PENGEMBANGAN LKS DISERTAI VIDEO ANIME PADA POKOK BAHASAN FLUIDA DINAMIK DI SMA - Ervina Ria Agustin; Sri Wahyuni; Maryani Maryani; Pramudya Dwi Aristya Putra (JURNAL PEMBELAJARAN FISIKA, 2017)
This research was a developmental research. The product of this research was inthe form of students’ worksheet or LKS along with anime video in the topic of fluiddynamic at senior high school. The model of this development was ADDIE (Analyze,Design, Development, Implementation and Evaluation). The research instruments used inthis research were in the form of validation sheet, critical thinking ability test, andstudents’ response questionnaire. Based on the validation results from the experts and theusers, it was known that the score for the LKS was 86,45% while for the anime video87,05%. Both of them were at the level of perfectly valid. The result of the pre-test andpost-test analysis showed that the average of N-gain score was 0,56 which was in themedium category. The students’ response of the use of LKS with anime video was 83,17%which was categorized as positive response.Key words: LKS, anime video, validation, students’ response, critical thinking.